Sloshing reduction in a pitching circular cylindrical container by multiple rigid annular baffles. (1st January 2019) - Wang, Jiadong; Wang, Chenglong; Liu, Jinxing
Abstract: Liquid sloshing is a problem of serious concern in partially liquid filled containers mounted in the moving vehicle or structure. An analytical technology is developed to solve the dynamic response of the liquid in the circular cylindrical container with multiple rigid baffles subjected to the pitching excitation. The generalized coordinates are introduced to expand the free surface elevation and the velocity potential, which contains the Stokes-Joukowski potential. Based on the partition of the liquid domain, a new method is developed to obtain the analytical solution of the Stokes-Joukowski potential. According to the kinematic and dynamic boundary conditions on the free surface, the dynamic response equation can be established. The analytical model for liquid sloshing is validated with the numerical results obtained from the commercial software ADINA. Systematic parametric investigations are carried out to reveal the effects of baffles' parameters and the pitching excitation frequency on the responses of the liquid.